Cytoplasmic LIF reprograms invasive mode to enhance NPC dissemination through modulating YAP1-FAK/PXN signaling - Liu, Shu-Chen; Hsu, Tien; Chang, Yu-Sun; Chung, An-Ko; Jiang, Shih Sheng; OuYang, Chun-Nan; Yuh, Chiou-Hwa; Hsueh, Chuen; Liu, Ya-Ping; Tsang, Ngan-Ming (Nature communications, 2018)
Metastasis remains a clinically unsolved issue in nasopharyngeal carcinoma. Here, we report that higher levels of cytoplasmic leukemia inhibitory factor (LIF) and LIF receptor are correlated with poorer metastasis/recurrence-free survival. Further, single nucleotide variations and signal peptide mutation of LIF are identified in NPC. Cytoplasmic LIF reprograms the invasive mode from collective to mesenchymal migration via acquisition of EMT and invadopodia-associated characteristics. Higher cytoplasmic LIF enhances cancer vascular dissemination and local invasion mechanistically through modulation of YAP1-FAK/PXN signaling. Immunohistochemical analyses of NPC biopsies reveal a positive correlation of cytoplasmic LIF expression with focal adhesion kinases. Pharmaceutical intervention with AZD0530 markedly reverses LIF-mediated cancer dissemination and local invasion through promotion of cytoplasmic accumulation of YAP1 and suppression of focal adhesion kinases. Given the significant role of LIF/YAP1-focal adhesion signaling in cancer dissemination, targeting of this pathway presents a promising opportunity to block metastasis. Molecular pathways regulating nasopharyngeal carcinoma (NPC) metastasis are unclear. Here they report higher levels of cytoplasmic leukemia inhibitory factor (cLIF) and LIF receptor (LIFR) to correlate with higher metastasis in NPC patients, and show cLIF to promote NPC metastasis and vascular dissemination via the YAP1-FAK/PXN axis.